2004
DOI: 10.1111/j.1523-1755.2004.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of renal allograft inflammation by measurements of mRNA for IP-10 and CXCR3 in urine

Abstract: Our investigation demonstrates that intragraft cellular events associated with acute rejection of human renal allografts can be noninvasively identified by measurements of mRNA for IP-10 and CXCR3 in urinary cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 47 publications
11
127
0
3
Order By: Relevance
“…Urinary measurements of MIG in a small number of pediatric patients (33) and in adult renal allograft patients support our data (34,35). Nevertheless, so far no study has shown the day-to-day value of urinary CXCR3 ligand measurements in a nonselected group of de novo NTX patients and the predictive value of MIG in urine for the diagnosis of AR.…”
Section: Discussionsupporting
confidence: 58%
“…Urinary measurements of MIG in a small number of pediatric patients (33) and in adult renal allograft patients support our data (34,35). Nevertheless, so far no study has shown the day-to-day value of urinary CXCR3 ligand measurements in a nonselected group of de novo NTX patients and the predictive value of MIG in urine for the diagnosis of AR.…”
Section: Discussionsupporting
confidence: 58%
“…The tests that are needed for this assessment ideally would be noninvasive, allowing for frequent sampling, and be capable of detecting subclinical inflammation with satisfactory sensitivity and specificity. The urine may be the ideal medium to look for candidate tests that may include the products of alloactivated or cytotoxic cells (46), chemokines and cytokines (47,48), the patterns of proteins detected by proteomic techniques (49), or those of low molecular weight metabolites detected by magnetic resonance (50). Detection of subclinical inflammation by these means may allow for the tailoring of the intensity of immunosuppression to the inflammatory status of the graft and result in the reduction of both the incidence of late allograft losses and the unwanted side effects of immunosuppressive therapy.…”
Section: Protocol Biopsies In Renal Transplant Patients: Future Direcmentioning
confidence: 99%
“…Sensibilidade de 71% e especificidade de 95% para o diagnóstico de RA foram atribuídas à dosagem urinária de IP-10/CXCL10 2 a 3 dias antes da bióp-sia renal. 57 Tatapudi et al 58 sugerem que a mensuração do RNA mensageiro para o IP-10/CXCL10 ou para o receptor de quimiocina CXCR3 em células urinárias pode tornar-se uma forma não invasiva de elucidar o tráfego celular durante os episódios de RA em enxertos renais humanos. Esses autores obtiveram 63 espécimes de urina de 58 transplantados submetidos à biópsia renal e 27 amostras urinárias de 24 indivíduos sem alteração de função renal.…”
Section: Citocinas E Quimiocinas No Tecido Renal E No Sangue De Transunclassified
“…Esses autores obtiveram 63 espécimes de urina de 58 transplantados submetidos à biópsia renal e 27 amostras urinárias de 24 indivíduos sem alteração de função renal. 58 Foi detectado que o nível de RNA mensageiro para o IP-10/CXCL10 ou CXCR3 prediz o tráfego celular intraenxerto, relacionando-se com a RA. 58 Resultados referentes ao aumento da expressão do RANTES/CCL5 urinário em presença de RA têm sido relatados por alguns autores.…”
Section: Citocinas E Quimiocinas No Tecido Renal E No Sangue De Transunclassified
See 1 more Smart Citation